Pengaruh Tax Avoidance, Ukuran Perusahaan Dan Leverage Terhadap Firm Value - Mega Putri Utami; Santi Octaviani; Entis Haryadi ("LAWSUIT" Jurnal Perpajakan, 2022)
This study aims to determine the effect of tax avoidance on firm value, company size on firm value and leverage on firm value and to determine the effect of tax avoidance, company size and leverage on firm value in Mining Sector Companies listed on the Indonesia Stock Exchange for the 2015-2020 period. This research was conducted using quantitative methods with an associative approach. The population of this study was 47 companies and 9 companies were sampled using the purposive sampling method. Data analysis using SPSS version 25. Based on the results, it can be partially concluded that: 1) Tax Avoidance has no significant effect on Firm Value, 2) Company Size has a significant influence on Firm Value, 3) Leverage has a significant influence on Firm Value. And based on the results simultaneously concluded that Tax Avoidance, Company Size and Leverage have a significant influence on Firm Value.